(untitled) (Eurasian Journal of Ecology, 2016)
Data on distribution of macrozoobenthos within Kazakhstan sector of the Caspian Sea in spring and autumn 2008 are presented. Based on the analysis of data on number of macrozoobenthos borderline between Northern and middle Caspian Sea in 2008 has been determined. Season dynamics of macrozoobenthos community is shown. Main factors affecting distribution of macrozoobenthos within water body under study are: water salinity, soil characteristics, and depth.